Designing the Gamification Framework to Increase Sales Motivation at PT XYZ - Yopi Putra, Ayu Puspitarini, Edi Yusuf Wirawan, Emil R. Kaburuan*, Gunawan Wang (International Journal of Control and Automation, 2020)
Improvement of the engagement and motivation of the sales force is needed to be considered since the revenue of most companies depends on the sales activities. The thought of gamification within the sales force activity is expected to be an answer because employees not only voluntarily contribute but are also involved and motivated in achieving personal and organizational goals. The aim of this study is to propose a gamification design that’s specific to sales activities used by sales team in a property sector. The study was taken place at PT XYZ as one of Indonesian company engaged in the property sector. The paper will discuss further about detail of requirement, system design, and the implementation plan of gamification in PT XYZ. The proposed design produced in this study is expected to be implemented in this company.